Pathogenic Inflammation and Its Therapeutic Targeting in Systemic Lupus Erythematosus - Gottschalk, Timothy A.; Tsantikos, Evelyn; Hibbs, Margaret L. (Frontiers in Immunology, 2015)
Systemic Lupus Erythematosus (SLE, lupus) is a highly complex and heterogeneous autoimmune disease that most often afflicts women in their child-bearing years. It is characterized by circulating self-reactive antibodies that deposit in tissues including skin, kidneys and brain, and the ensuing inflammatory response can lead to irreparable tissue damage. Over many years, clinical trials in SLE have focused on agents that control B and T lymphocyte activation, and, with the single exception of an agent known as Belimumab which targets the B cell survival factor BAFF, they have been disappointing. At present, standard therapy for SLE with mild disease is the agent hydroxychloroquine. During disease flares, steroids are often used, while the more severe manifestations with major organ involvement warrant potent, broad-spectrum immuno-suppression with cyclophosphamide or mycophenolate. Current treatments have severe and dose-limiting toxicities and thus a more specific therapy targeting a causative factor or signaling pathway would be greatly beneficial in SLE treatment. Moreover, the ability to control inflammation alongside B cell activation may be a superior approach for disease control. There has been a recent focus on the innate immune system and associated inflammation, which has uncovered key players in driving the pathogenesis of SLE. Delineating some of these intricate inflammatory mechanisms has been possible with studies using spontaneous mouse mutants and genetically engineered mice. These strains, to varying degrees, exhibit hallmarks of the human disease and therefore have been utilized to model human SLE and to test new drugs. Developing a better understanding of the initiation and perpetuation of disease in SLE may uncover suitable novel targets for therapeutic intervention. Here we discuss the involvement of inflammation in SLE disease pathogenesis, with a focus on several key proinflammatory cytokines and myeloid growth factors, and review the known outcomes or the potential for targeting these factors in SLE.